Neutrophil extracellular traps and neutrophil-related mediators in human thyroid cancer - Modestino, Luca; Cristinziano, Leonardo; Poto, Remo; Ventrici, Annagioia; Trocchia, Marialuisa; Ferrari, Silvia Martina; Fallahi, Poupak; Paparo, Sabrina Rosaria; Marone, Gianni; Antonelli, Alessandro; Varricchi, Gilda; Galdiero, Maria Rosaria (Frontiers in Immunology, 2023)
Background: Polymorphonuclear neutrophils (PMNs) are the main effector cells in the inflammatory responses and play multiple roles in thyroid cancer (TC). PMNs contain and release a plethora of mediators, including granular enzymes [e.g., myeloperoxidase (MPO), pentraxin-3 (PTX3) and matrix metalloproteinase-9 (MMP-9)], and neutrophil extracellular traps (NETs). The aim of this study was to evaluate NETs and neutrophil-derived mediators as possible biomarkers in TC patients. Methods: 20 patients with differentiated thyroid cancer (DTC), 26 patients with dedifferentiated thyroid cancer (De-DTC), 26 patients with multinodular goiter (MNG) and 22 healthy controls (HCs) were recruited. Serum concentrations of free DNA (dsDNA), nucleosomes, and citrullinated histone H3 (CitH3) and MPO-DNA complexes were evaluated as NET biomarkers. Neutrophil-related mediators such as MPO, PTX3, MMP-9, CXCL8, and granulocytemonocyte colony-stimulating factor (GM-CSF) were measured by ELISA. Results: Serum levels of all three four NET biomarkers were increased in DeDTC patients compared to HCs. CitH3 serum levels were selectively increased in both DeDTC and DTC patients compared to HCs and MNG patients. MPO-DNA complexes and Nnucleosomes were selectively increased only in DeDTC patients compared to HCs and MNG patients. Moreover, MPO-DNA complexes were selectively increased in DeDTC patients compared to DTC patients also. MPO circulating levels were selectively increased in the DeDTC patient subgroup compared to HCs. Circulating levels of PTX3, MMP-9 and GM-CSF were increased in DTC and DeDTC patients compared to HCs. Nucleosomes positively correlated with dsDNA, CitH3, MPO and CXCL8. MPO-DNA complexes positively correlated with dsDNA, CitH3, CXCL8, MPO and nucleosome levels. Moreover, threewo out of the fourthree NET biomarkers (i.e., dsDNA, and nucleosomes and MPO-DNA complexes) were increased in elderly patients compared to young patients and in patients with metastatic disease at diagnosis compared to non metastatic patients. Nucleosomes were higher in males compared to females. and in patients with metastatic disease at diagnosis. Conclusions: MPO-DNA complexes, nNucleosomes and, to some extent, CitH3 levels seem to correlate with malignancy and severity of progressive TC. Moreover, serum concentrations of PMN-related mediators (MPO, PTX3, GM-CSF) were increased in TCs compared to MNG and HCs.